Serum extracellular vesicles—a promising path towards an individualized medicine in primary sclerosing cholangitis and related cholangiocarcinoma - Schröder, Torsten; Sina, Christian (Journal of Laboratory and Precision Medicine, 2017)
Primary sclerosing cholangitis (PSC) is a chronic inflammatory disease of the biliary tract system, whose mechanisms of pathogenesis remain elusive. Most importantly, PSC is considered a major medical burden due to its premalignant nature (1). Malignant complications in PSC frequently occur within the hepatobiliary system, arising predominately as cholangiocarcinoma (CCC) (2).